Pharmacological inhibition of the triggering receptor expressed on myeloid cells‐1 limits reperfusion injury in a porcine model of myocardial infarction. (June 2015) - Lemarié, Jérémie; Boufenzer, Amir; Popovic, Batric; Tran, Nguyen; Groubatch, Frederique; Derive, Marc; Labroca, Pierre; Barraud, Damien; Gibot, Sébastien
Abstract Aims Limitation of ischemia/reperfusion injury is a major therapeutic target after acute myocardial infarction (AMI). Toll‐like receptors are implicated in the inflammatory response that occurs during reperfusion. The triggering receptor expressed on myeloid cells (TREM)‐1 acts as an amplifier of the immune response triggered by toll‐like receptor engagement. We hypothesized that administration of a TREM‐1 inhibitory peptide (LR12) could limit reperfusion injury in a porcine model of AMI. Methods and results AMI was induced in 15 adult minipigs by a closed‐chest coronary artery occlusion‐reperfusion technique. Animals were randomized to receive LR12 or vehicle before reperfusion (LR12 n = 7, vehicle n = 8), and were monitored during 18 h. AMI altered hemodynamics and cardiac function, as illustrated by a drop of mean arterial pressure, cardiac index, cardiac power index, ejection fraction, and real‐time pressure–volume loop‐derived parameters. TREM‐1 inhibition by LR12 significantly improved these dysfunctions (P < 0.03) and limited infarct size, as assessed by lower creatine phosphokinase and troponin I concentrations (P < 0.005). Pulmonary, renal, and hepatic impairments occurred after AMI and were attenuated by LR12 administration as assessed by a better PaO2 to FiO2 ratio, a less positive fluid balance, and lower liver enzymes levels (P < 0.05). Conclusion Inhibition of the TREM‐1 pathway by a synthetic peptide limited myocardial reperfusion injury in a clinically relevant porcine model of AMI.